Effectiveness of technology-enhanced teaching methods of undergraduate dental skills for local anaesthesia administration during COVID-19 era: students' perception - Rasa Mladenovic; Sakher AlQahtani; Kristina Mladenovic; Zoran Bukumiric; Sobia Zafar (BMC, 2022)
Abstract Background Traditional face-to-face clinical learning became problematic for final year dental students during the COVID-19 pandemic. Distance-learning may help mitigate the immediate impact of dental school closures. Integrating e-learning technologies into the learning process helps bridge the gap between pre-clinical and clinical training. Simulation allows students to repeat procedures until they demonstrate acceptable levels of skill. This study aimed to determine the effectiveness of a serious game as an additional teaching tool during the COVID-19 era to improve dental students' local anaesthesia administration technique and confidence. Methods This study applied a simulation-based serious game as an additional learning tool for training and educating dental students in local anaesthesia. Students used a mobile simulator in Serbian for 10 days from their homes. To evaluate the learning process, the students completed a post-training questionnaire. Results All respondents felt comfortable using the simulator. Over 90% of respondents believed that the application facilitated the learning process and had advantages in terms of accessibility and ease of use. Also, students found augmented reality (AR) technology particularly interesting to use. The use of a mobile simulator designed as a 3D and AR environment allows for simpler localisation and identification of anatomical structures and reference points, which is a good base for clinical practice. Conclusion Serious games of local anaesthesia procedures as an additional e-learning tool during the COVID-19 era could improve students' knowledge and skills.